Book review: Tejubehan, Salai Selvam, & V. Geetha (Trans.), Drawing from the City. (November 2019) - Moharir, Mitali
Tejubehan, Salai Selvam, & V. Geetha (Trans.), Drawing from the City . Chennai: Tara Books, 2017, 32 pp., ₹499. ISBN: 9789383145966.